Quality of E-KTP (ID card) Making Services in West Cikarang Regency, Bekasi Regency - Sumarna, Faiza Adzani; Kurniati, Poni Sukaesih (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
Population administration services are the government’s obligation to empower citizens’ identity rights through the provision of electronic Identity Cards (E-KTP) at the sub-district level. This paper will analyze the quality of E-KTP services in West Cikarang Regency, Bekasi Regency based on scientific findings and relevant secondary data. Methodologically, this study relies on secondary research, using a literature review and descriptive analysis of scientific journals, books, and official documents related to population administration services. The results of the study show that the quality of E-KTP services in West Cikarang Regency is in the category of quite good. However, problems related to the timeliness of service, availability of facilities and consistency of equipment service are still observed. The main conclusion of this study is that improving the quality of E-KTP services must be a sustainable effort through the empowerment of service governance, increasing equipment capacity and optimizing facilities and infrastructure. It is hoped that the results of this research can be used as an academic reference and evaluation material for local governments in formulating policies to improve the quality of population administration services.